PENGARUH PENGGUNAAN MEDIA GEOBOARD TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS IV SD NEGERI 185 PALEMBANG - Suci Paranita, Putri; Arni, Yusni; Dedy, Adrianus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of geoboard media on the mathematical conceptual understanding of class IV students at SD Negeri 185 Palembang. This study employed a quantitative experimental method using a True-Experimental design with a Posttest-Only Control Design. The population consisted of 103 class IV students of SD Negeri 185 Palembang distributed across four classes. The sample was selected using a simple random sampling technique, resulting in class IV.A as the experimental group and class IV.B as the control group, with 25 students in each class. Data were collected through an essay test on mathematical conceptual understanding and documentation. Data analysis was conducted using normality testing, homogeneity testing, and hypothesis testing through the Independent Sample T-Test assisted by SPSS version 26. The results showed that the mean posttest score of the experimental class was 69.9960, while the mean score of the control class was 52.8296. The hypothesis testing results indicated that the Sig. (2 tailed) value was 0.000 < 0.05; therefore, H₀ was rejected and Hₐ was accepted, indicating a significant difference in mathematical conceptual understanding between students in the experimental class and those in the control class. It can be concluded that the use of geoboard media has a significant effect on the mathematical conceptual understanding of class IV students at SD Negeri 185 Palembang.